Biotechnological Production of Poly(3-Hydroxybutyrate-co-4-Hydroxybutyrate-co-3-Hydroxyvalerate) Terpolymer by Cupriavidus sp. DSM 19379 - Kucera, Dan; Novackova, Ivana; Pernicova, Iva; Sedlacek, Petr; Obruca, Stanislav (Bioengineering (Basel, Switzerland), 2019)
The terpolymer of 3-hydroxybutyrate (3HB), 3-hydroxyvalerate (3HV), and 4-hydroxybutyrate (4HB) was produced employing Cupriavidus sp. DSM 19379. Growth in the presence of γ-butyrolactone, ε-caprolactone, 1,4-butanediol, and 1,6-hexanediol resulted in the synthesis of a polymer consisting of 3HB and 4HB monomers. Single and two-stage terpolymer production strategies were utilized to incorporate the 3HV subunit into the polymer structure. At the single-stage cultivation mode, γ-butyrolactone or 1,4-butanediol served as the primary substrate and propionic and valeric acid as the precursor of 3HV. In the two-stage production, glycerol was used in the growth phase, and precursors for the formation of the terpolymer in combination with the nitrogen limitation in the medium were used in the second phase. The aim of this work was to maximize the Polyhydroxyalkanoates (PHA) yields with a high proportion of 3HV and 4HB using different culture strategies. The obtained polymers contained 0-29 mol% of 3HV and 16-32 mol% of 4HB. Selected polymers were subjected to a material properties analysis such as differential scanning calorimetry (DSC), thermogravimetry, and size exclusion chromatography coupled with multi angle light scattering (SEC-MALS) for determination of the molecular weight. The number of polymers in the biomass, as well as the monomer composition of the polymer were determined by gas chromatography.
Keywords: Cupriavidus malaysiensis; polyhydroxyalkanoates; P(3HB-co-3HV-co-4HB); terpolymer